Improving Students’ Vocabulary By Using Board Games With The Contextual Teaching And Learning Method At SD Bali Bilingual School - Ni Luh Ratna Rapiasih; Luh Made Dwi Wedayanti; Pande Agus Adiwijaya (CV. Tirta Pustaka Press, 2024)
This research is a classroom action research (PTK) which aims to improve students' vocabulary through learning media using board games in class IV A of Bali Bilingual School elementary school. The subjects of this research were all students of class IV A which amounted to 17 students. While the object of this research is to improve students' vocabulary by using board games with contextual teaching and learning methods at Bali Bilingual School elementary school. This research was carried out with steps namely planning, implementing, observing and reflecting. The data of the research were analyzed descriptively with 2 types of data, namely quantitative data and qualitative data. The results of the initial test showed that the average score of students' vocabulary skills was only 64 which was in the low category with a classical 42%. After the research was conducted in cycle I, there was an increase in the students' average score to 79 which is included in the sufficient category with 88% classical in cycle II. Based on the result, it can be concluded that board game technique can improve students' vocabulary skill in class IV A of Bali Bilingual School.